Mixed-methods investigation of barriers and needs in mental healthcare of adults with autism and recommendations for future care (BarrierfreeASD): study protocol. Issue 8 (23rd August 2022) - David, Nicole; Dückert, Sophia; Gewohn, Petia; König, Hannah; Rahlff, Pascal; Erik, Frank; Vogeley, Kai; Schöttle, Daniel; Konnopka, Alexander; Schulz, Holger; Peth, Judith
Abstract : Introduction: Autism refers to an early-onset neurodevelopmental condition with characteristic impairments and difficulties in practical living skills, which persist across the lifespan such that adults with autism often require substantial support and comprehensive care. Yet, mental health and other services are frequently unavailable for adults with autism despite considerable need for mental healthcare and individual, familial and socioeconomic burdens. This study will (1) examine current needs, barriers and burdens related to ineffective healthcare of adults with autism in Germany, (2) develop specific recommendations for a need-oriented mental healthcare model and (3) evaluate its future implementation. Methods and analysis: A mixed-methods design with three phases will be conducted. In phase 1, current mental healthcare for adults with autism will be assessed at three levels (individual, structural and professional) and from three perspectives (adults with autism, relatives and healthcare providers) using (1) focus groups/interviews (qualitative data) and (2) large-scale online surveys (quantitative data). Furthermore, service utilisation and related costs will be estimated. In phase 2, recommendations for a future healthcare model will be derived based on phase 1, considering the heterogeneous and complex needs within the autism spectrum and specifying indications for recommended services. In phase 3, these will again be evaluated by the three stakeholder groups using mixed-methods and analysed regarding feasibility of implementation and cost-effectiveness. Our study will, thus, contribute to a better translation of recommendations into practice to reduce disability, burden and costs related to ineffective healthcare and improve mental health outcomes for adults with autism and those who support them. Ethics and dissemination: This study was approved by the Local Psychological Ethics Commission of the Center for Psychosocial Medicine at the University Medical Center Hamburg-Eppendorf (LPEK-0227). Findings will be disseminated via scientific meetings and peer-reviewed journals. Cooperating partners and associations will be informed about the study's course and findings by regular newsletters and meetings. Trial registration number: This study protocol was preregistered at the Open Science Framework (osf.io/5x8pg).